Linking safety nets, social protection, and poverty reduction: directions for Africa - Adato, Michelle; Ahmed, Akhter; Lund, Francie (International Food Policy Research Institute, 2004)
In Africa and elsewhere, safety nets were promoted in the 1980s as a response to the (presumably short-term) adverse effects of structural adjustment. Though some safety nets had a developmental component, safety nets are still largely associated with the idea of a short-term buffer. “Social protection” is a newer term that incorporates safety net programs but also includes a role for renewed state involvement, emphasizes a longer-term developmental approach, includes social assistance and social insurance, and is often advocated as a right rather than a reactive form of relief. Social protection policy addresses not only programs aimed at reducing the impact of shocks and coping with their aftermath, but also interventions designed to prevent shocks and destitution in the first place. Most societies have private interhousehold, intrafamily, and intrahousehold transfers that promote resilience to shocks, mitigating their negative effects. However, in countries or communities where people are universally poor, there is less to share, particularly in times of shocks that affect all or many in the society (such as drought, floods, AIDS, or widespread structural unemployment) — which is precisely when the need for help is most critical. -- from Text